Don't Interrupt! A Case Report of Continuing Peritoneal Dialysis After Endoscopic Gastric Tumor Resection. Issue 1 (November 2019) - Silverstein, William K.; Teshima, Christopher; Jolly, Simran; Perl, Jeffrey
Rationale: The evidence supporting the safety of restarting peritoneal dialysis (PD) immediately after abdominal surgery and interventions is scant. In particular, there are no reported cases characterizing periprocedural management of PD for patients undergoing endoscopic submucosal dissection for gastric intramucosal tumor removal. Presenting concerns of the patient: A 66-year-old female with end-stage kidney disease secondary to diabetic nephropathy, currently on nocturnal automatic PD, presented with new iron-deficiency anemia. Workup revealed an intramucosal gastric lesion proximal to the pylorus, without surrounding lymph node involvement. Endoscopic submucosal dissection was performed with en bloc endoscopic resection of a 5-cm, partially flat, partially sessile mass along the posterior wall and lesser curvature of the gastric antrum. Pathology revealed low-grade dysplasia without features of malignancy. There was no evidence of hemorrhage or leak post-dissection. Diagnoses: The clinical presentation was consistent with an uncomplicated endoscopic submucosal dissection. Interventions: Peritoneal dialysis was held for 48 hours and restarted thereafter with no complications. The patient did not require bridging with hemodialysis. Outcomes: The patient had an uncomplicated post-endoscopic course, with no subsequent episodes of PD-associated peritonitis after at least 6-month follow-up. Novel finding: This is the first reported case of PD reinitiation after endoscopic submucosal dissection of a gastric tumor.